collages, décollages, images détournées : Rencontres d'Art 1992. - Tuffelli, Nicole; Duchein, Paul; Arnaud, Noël; Monnin, Françoise; Musée Ingres, Montauban; Musée des Beaux-Arts, Pau ([S.a.] : [s.l.], 1992)
Dufresny, Charles ; Arnaud, Noël, Bozzolini, Silvano ; Bucaille, Max ; Buraglio, Pierre ; Burles, Michèle ; de Cambiaire, Christian ; Chaissac, Gaston ; Coaquette, Ivan ; Dérieux, Roger ; Didier, Jérôme ; Dorny, Bertrand ; Drai, Claudine ; Dubuffet, Jean ; Duchamp, Marcel ; Duchein, Paul ; Dufrêne, François ; Ellouet, Aube ; Ernst, Max ; Erro, Gudmunder ; Estève, Maurice ; Ethuin, Anne ; Gaillard, Philippe et. al
7 mai - 7 juin Musée Ingres, Montauban - Saison d'été, Musée des Beaux-Arts, Pau
kunstcatalogus